Boosting the Performance of La0.8Sr0.2MnO3-δ Electrodes by The Incorporation of Nanocomposite Active Layers - Zamudio-García, Javier; Caizán-Juanarena, Leire; Porras-Vázquez, José Manuel; Losilla, Enrique R.; Marrero-López, David (Wiley, 2022)
The use of active layers is a promising strategy to improve the properties of air electrodes for solid oxide fuel cells (SOFCs). In this work, La0.8Sr0.2MnO3-δ is combined with different oxide ion conductors Ce0.9Gd0.1O1.95, Bi1.5Y0.5O3 and Pr6O11 to form highly efficient nanocomposite active layers in a single step by spray-pyrolysis deposition. One of the main advantages of these nanocomposite layers is that the nanoscale microstructure is retained at relatively high sintering temperatures. As a consequence, the interfacial area between the electrode and the electrolyte increases significantly, leading to fast oxide ion transport at the interface, as well as more active sites for the electrochemical reactions. An exhaustive structural, microstructural, and electrochemical characterization of the layers are performed to evaluate their potential use in SOFCs. The incorporation of a La0.8Sr0.2MnO3-δ-Ce0.9Gd0.1O1.95 (LSM-CGO) interlayer decreases the polarization resistance of LSM cathode from 1.71 to 0.46 Ω cm2 at 700 °C. Moreover, a single cell with LSM-CGO interlayer generates a peak power density of 1.20 W cm–2 at 800 °C compared to 0.79 W cm–2 for the same cell without active layer. These results demonstrate the great benefits of using nanocomposite layers to improve the properties of air electrodes.
Keywords: Electrodos; nanocomposite